FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK TERHADAP MEMBAYAR PBB-P2 PADA KELURAHAN PASIR IMPUN KECAMATAN MANDALAJATI KOTA BANDUNG TAHUN 2021 - Meilinda Kartika Putri; Paul Eduard Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2022)
This study aims to determine whether tax returns, tax services, taxpayer awareness, and tax sanctions both partially and simultaneously affect taxpayer compliance. The population in this study were 2433 rural and urban land and building taxpayers registered in Pasir Impun Village, Mandalajati District, Bandung City. The analytical tool in this study uses multiple linear regression analysis. Based on the results of the study, it shows that the tax return, tax services, taxpayer awareness and tax sanctions have a significant effect on taxpayer compliance. Based on the results of the correlation coefficient test, the adjusted R square value was obtained at 0.423 so that it can be concluded that the percentage contribution of the variable tax return, tax services, taxpayer awareness and tax sanctions is 42.3% even as the last57.7% prompted through other variables.